AN INTEGRATIVE APPROACH BETWEEN GAME THEORY AND PARETO FRONTIER CONCEPTS FOR THE TRANSBOUNDARY WATER RESOURCES ALLOCATIONS: Case of the Euphrates and Tigris - Mehmet Kucukmehmetoglu (European Regional Science Association (ERSA), 2010)
In the transboundary water resources allocation issues, there has been so far very limited progress made in terms of allocation techniques. This study introduces a composite water resources allocation approach that integrates both game theory and Pareto frontier technique over the case of the Euphrates and Tigris. The proposed approach searches an acceptable solution set over the Pareto frontier surface via game theory based core constraints. The base model to generate the Pareto Frontier Surface is the Euphrates and Tigris River Basin Model, which is a linear programming model maximizing net economic benefits while optimally allocating scarce water resources in the basin. Results show that i) game theory provides a determinative backbone for an efficient and effective use of Pareto Frontier Surface and ii) upstream countries have upper hand position due to the geographic context.
Keywords: 330; Linear programming; Multi-objective programming; Game theory; Pareto frontier surface; Transboundary water resources allocation; the Euphrates and Tigris